A novel test setup for the characterization of bridging behaviour of single microfibres embedded in a mineral-based matrix. (September 2018) - Ranjbarian, Majid; Mechtcherine, Viktor
Abstract: The mechanical performance of fibre-reinforced, mineral-based composites, such as strain-hardening cement-based composites (SHCCs), is determined to a great extent by the bonding between dispersed fibres and matrix and the corresponding bridging action of fibres crossing cracks. To characterize such interactions between fibre and matrix, single fibre pull-out tests in a single-sided configuration are usually performed. Such tests are relatively simple and straightforward, but they have some major limitations. To overcome these limitations, a novel setup is suggested in the article at hand. First, setting up, preparation of specimens, testing procedure and data evaluation are described in detail. Then, the results obtained in the quasi-static monotonic tests on individual PVA microfibres embedded in a fine-grained, cement-based matrix are presented and discussed under consideration of corresponding results gained by conventional single-sided fibre pull-out tests on specimens made of the same constituents. Next, the experiments with the new setup are performed at a higher displacement rate so that the rate effect on the pull-out force-crack opening behaviour can be investigated. Finally, the applicability of the new setup for testing fatigue behaviour of the composite on the micro-scale is demonstrated by means of cyclic tests in tension-compression regime. Such tests cannot be performed using conventional fibre pull-out tests.